(untitled) (GENDER EQUALITY: International Journal of Child and Gender Studies, 2024)
Gender inequality is a persistent issue experienced by women worldwide, often intertwined with their limited participation in political spheres. This study examines the political involvement of women in the parliaments of Indonesia and the United States of America (USA) through the lens of liberal feminism theory. Employing qualitative decryption approaches with a comparative study design, data collected from both the Indonesian Parliament and the USA Parliament were understood, recorded, phrased, compared and analyzed within the framework of liberal feminism theory, focusing on the "Right in Public Life and Politics". The results of the study revealed that while the Government of Indonesia has enacted legislation mandating a minimum of 30% female representation in political parties, both the Indonesian and US parliaments exhibit disproportionately low levels of female members compared to their male counterparts. A notable distinction between the two lies in the parliamentary leadership, with Indonesia being led by a woman and the USA by men. To enhance women’s political participation, it is imperative for both governments to rigorously enforce regulations and sanctions against political parties. Additionally, efforts to dismantle the prevailing masculine culture in various societies are crucial in order to foster gender equality and justice, thereby realizing gender democracy.